Inside Tutor Capabilities Utilizing Media Training Learning Bridal - Purba, Theresia Okta Veralita (Universitas Negeri Padang, 2021)
Tutor's Ability to Utilize Learning Media for Bridal Makeup Training Program at LKP Ulfah Karawang. The ability of tutors to use instructional media at the time of implementation is already in the skilled stage. In conducting the training there are three stages, namely planning, implementation and evaluation. The cosmetology training plan includes initial preparation with activities that include preparing modules as teaching material to be delivered by tutors, reviewing the material to be delivered and preparing examples of Sundanese-style bridal fashion and facial sketch media. In the implementation of tutors utilizing media that has been prepared beforehand, and in the delivery of material the tutor uses examples of Sundanesestyle bridal clothing and facial sketch media. The next stage is evaluation, the evaluation is centered on the tutor because only the tutor evaluates. Evaluation is carried out at each meeting to determine the ability of learning citizens. The overall evaluation was conducted at the last meeting, namely the makeup competency test. The overall evaluation phase tutors judge based on the results because if the results are appropriate then the makeup technique is correct and the media utilization is correct. The inhibiting factor in utilizing the learning media of LKP Ulfah's bridal make up training program comes from internal and external factors. Internal factors that arise obstacles are the nature of what it is in utilizing learning media, while the external factor is the limited space and the limited media used. In preparation, implementation and follow-up in utilizing tutor learning media is less than optimal.Keywords: the ability of tutors, learning media